MicroRNA-488-3p-loaded engineered exosomes inhibit proliferation, migration and invasion of hepatocellular carcinoma by targeting SEC61G - Huijie Gao; Zhaobin He; Shengbiao Yang; Xiqiang Wang; Qisen Yan; Chao Gao; Naiqing Liu; Zhaoyang Zhang; Weibo Niu; Jun Niu; Cheng Peng (PLoS ONE, 2026)
SEC61G is an oncogene in hepatocellular carcinoma (HCC), a common malignant tumor worldwide. MicroRNAs (miRNAs) regulation of oncogenes are available therapeutic strategies being investigated in HCC, but the effective miRNA delivery remains a challenge. Here, we investigated the potential therapeutic effects of miRNA-loaded engineered exosomes in patients with HCC. MiRNAs that could bind to SEC61G were screened using Targetscan, and were verified using HepG2 cells viability after transfecting miRNAs mimic. Five miRNAs binding to SEC61G,among which, miR-651-3p and miR-488-3p mimic significantly inhibited HepG2 cells viability (p < 0.05) and decreased SEC61G protein expression. Then, dual-luciferase reporter assay also confirmed SEC61G as a target of miR-488-3p in HCC. After that, miR-488-3p-loaded engineered exosomes (Exo-miR-488-3p) were isolated from the supernatant of 488-3p-overexpressed cells and identified via nanoparticle tracking analysis, transmission electron microscopy and western blot. In vitro experiments showed that exo-miR-488-3p significantly inhibited proliferation, colony formation, migration and invasion of HepG2 cells than corresponding negative control. In addition, Exo-miR-488-3p tended to induce HepG2 cells apoptosis, though this relationship was not statistically significant. In conclusion, exo-miR-488-3p inhibits the malignant cytological activities in HCC, a possible strategy in the treatment of HCC.